Analisis Kebijakan Pemerintah Daerah Bidang Pertambangan di Kota Samarinda - Siti Airinda Marennu (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2019)
This study aims to describe the implementation of the regional government policy in mining in the city of Samarinda, the impact of these policies in the socio-economic life and community life in the city of Samarinda and outlines the role of the government in overcoming socio-economic and enviromental impacts in people‘s lives. The research method used is qualitative research methods by describing and explaining research results in writing. Data collevtion is done using literature study techniques, observation, intrviews, and online data search. This study describes the Implementation of Regional Government Policies in Mining in the City of Samarinda, The implementation of policies implemented by the regional government is the Granting of Mining, Development, Community Conflict Business Licensing and Environmental Impact Monitoring of Mining Businesses, in the implementation of these policies is carried out quite well although the implementation is still not maximal because the implementation of the policy in this case the settlement of local government conflict is still lacking. The government's efforts in implementing mining policies should be more in favor of the interests and welfare of the community. Impact of the Local Government's Mining Policy in Samarinda City illustrates that the implementation of the policy if carried out seriously will have a more positive impact, but in its implementation the resulting impact is more directed to negative impacts such as environmental pollution, flooding, air pollution to noise this is because the government does not side with the interests and goodness of the community.